Кот Котофеич - Ившин Вениамин Никонорович (Сказки для малышей, 2016)
Экземпляры: ф16 (20171010) / Инвентарный номер: 54697 / Цена: 85.00 / Сис.шифр: Д / Авт.знак: К 73 / ГРНТИ: 17.82.93 / ББК: 82.3(2Рос=Удм)